An experimental and theoretical study of duplex fcc+hcp cobalt based entropic alloys - Wang, Wei; Hou, Ziyong; Lizárraga, Raquel; Tian, Ye; Babu, R. Prasath; Holmström, Erik; Mao, Huahai; Larsson, Henrik (Acta materialia, 2019)
Martensitically formed duplex fcc + hcp Co-based entropic alloys have been investigated both experimentally and theoretically. Theoretical predictions are in good agreement with experimental observations. A fair correlation is found between calculated driving forces for a partitionless fcc→hcp transformation and experimentally obtained phase fractions. [Display omitted]